MENENTUKAN STRATEGI KOMPETITIF PENGGILINGAN PADI (RICE MILLING UNIT) UD. TANI JAYA DENGAN MENGGUNAKAN ANALISIS SWOT DI DESA NYAMPLUNG SARI, KECAMATAN PETARUKAN KABUPATEN PEMALANG, JAWA TENGAH - Daryo, Mr.; Jalil, Mahben (PERMANA, 2016)
Determining the Competitive Strategy of Rice Milling Unit UD. Tani Jaya Using SWOT Analysis in Nyamplung Sari Village, Petarukan District, Pemalang Regency, Central Java ". Essay. Tegal: Faculty of Economics, Pancasakti University Tegal. 2017. The purpose of the study was to analyze the UD strategy. Tani Jaya in achieving competitive advantage by using SWOT analysis. Data collection methods used in the study are interviews, documentation, literature. While the data analysis methods used are descriptive analysis, industry analysis, consumer valuation analysis, matrix analysis of internal strategy factors and external strategy factors (IFS-EFS) and SWOT Analysis Phase. From the results of rating (rating) the results of identification of strengths and weaknesses as internal strategic factors obtained a value of 2,922 with the criteria of being. The results of rating (rating) the results of identification of strengths and weaknesses as external strategic factors obtained a value of 2.896 with the criteria being. Total scores from internal and external factors are mapped into internal and external matrices, the current position of the company is in cell V, namely growth / stability.Keywords: SWOT Analysis